Are Bigger Banks Better? Firm-Level Evidence from Germany - Kilian Huber (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The effects of large banks on the real economy are theoretically ambiguous and politically controversial. I identify quasi-exogenous increases in bank size in postwar Germany. I show that firms did not grow faster after their relationship banks became bigger. In fact, opaque borrowers grew more slowly. The enlarged banks did not increase profits or efficiency, but worked with riskier borrowers. Bank managers benefited through higher salaries and media attention. The paper presents newly digitized microdata on German firms and their banks. Overall, the findings reveal that bigger banks do not always raise real growth and can actually harm some borrowers.
Keywords: E24; E44; G21; G28; 330